Impacto familiar de la sedación paliativa en pacientes terminales desde la perspectiva del cuidador principal - Carmona Jiménez, Ana María; González, Melina; Vélez Ángel, María Clara; Krikorian, Alicia (Psicooncología, 2017)
Objective: The present study aimed at describing the impact that palliative sedation had on the family and their subsequent bereavement process, from the primary caregiver´s point of view.Methodology: Qualitative study with a phenomenological approach; ten primary caregivers of patients with terminal illness who were treated by the palliative care group of an oncological institution in Medellin, Colombia and died under palliative sedation were interviewed. The information was analyzed using predetermined categories: meaning, emotional changes, structural changes and bereavement.Results: Caregivers had no prior knowledge about palliative sedation. All of them reported to be informed about the possible changes that patients could go through. However, half of the caregivers reported that the information was insufficient to understand the process they were facing. They expressed multiple feelings (relief, doubt, helplessness and sadness) before, during and after palliative sedation. Regarding structural changes, all families underwent reorganization, and family relationships were strengthened. On the whole, caregivers bereavement while relieving suffering and allowing a good death.Conclusions: Caregivers considered that the experience of palliative sedation was positive and satisfactory, allowing to relief suffering of their loved one and the family. It also eased the bereavement process as families made a positive reconstruction of the experience, strengthening their relationships and leaving a good memory of the patient’s death.
Keywords: Palliative care; terminal care; deep sedation; caregiver; family; bereavement.